Preservation of Marine Chemical Signatures in Upper Devonian Carbonates of Kinta Valley, Peninsular Malaysia: Implications for Chemostratigraphy - Haylay Tsegab Gebretsadik, Chow Weng Sum, Aaron W Hunter, . (2015)
The Kinta Limestone is an important Silurian to Permian age unit in the Western Belt of Peninsular Malaysia. Diagenetic alteration and thermal alteration, owing to adjacent igneous intrusion, have obscured many primary sedimentary features and primary geochemistry of the Kinta Limestone. Petrographic and geochemical analyses indicate, however, that some locations of this unit may contain textural and chemical indicators of primary marine properties.